KOMPETENSI TIM UNTUK PENINGKATAN KINERJA TIM PADA ORGANISASI POLITEKNIK ILMU PELAYARAN SEMA - Hendrawan, Andi; Indriyani; Hendrawan, Aji Kusumastuti (Jurnal Ilmiah Kemaritiman Nusantara, 2024)
Team competition is a necessity in an organization, both maritime and non-maritime, this will result in better and more effective team performance. This research is quantitative research by examining the relationship and influence of competence on team performance. The test results show the influence of team competency on t performance